Effects of public expenditures on environmental pollution: evidence from G-7 countries - Ozyilmaz, Ayfer; Bayraktar, Yuksel; Olgun, Mehmet Firat (Springer Science and Business Media LLC, 2023)
In this study, the effect of public expenditures and, their sub-components on environmental pollution is discussed in G-7 countries. Two different periods were used in the study. These are the period 1997-2020 for general public expenditure, and the period 2008-2020 for public expenditure sub-components. For cointegration, Westerlund cointegration test was used, and according to the analysis result there is a cointegration relationship between general government expenditure and environmental pollution. Panel Fourier Toda-Yamamoto causality test was used to determine the causality relationship between public expenditures and environmental pollution and the result indicates that there is bidirectional causality between public expenditures and CO2 on a panel basis. For models estimation, System the Generalized Method of Moments (GMM) method was used. The findings of the study indicate that general public expenditures decrease environmental pollution. Considering at the results of the sub-components of public expenditures, housing and community amenities, social protection, health expenditure, economic affairs, recreation, culture & religion expenditures have a negative effect on environmental pollution. Other control variables generally  have a statistically significant effect on environmental pollution. Energy consumption and population density increase environmental pollution but environmental policy stringency index, renewable energy and GDP per capita reduce environmental pollution.
Keywords: Economic Development; Carbon Dioxide; Health Expenditures; Environmental Pollution; Public Expenditures; 13. Climate action; 3. Good health